Loyalitas Karyawan: Pengaruh Kompensasi, Lingkungan Kerja dan Beban Pekerjaan pada BPR Weleri Makmur Pati - Wanuri Wanuri; Achmad Junaidi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
Employee loyalty is an employee's willingness to be loyal to the company where he works to carry out his responsibilities so that the company's goals can be achieved. The researcher found several complaints about lack of compensation, unsupportive work environment, high workload and low employee loyalty levels which can be seen at insignificant turnover rates. This study aims to determine the influence of compensation, work environment and workload on employee loyalty at BPR Weleri Makmur. The population in this study is 198 employees of BPR Weleri Makmur. The sampling method used was probability sampling with an accidental sampling technique and the number of samples was prepared by 100 respondents based on the Lemeshow formula. The data analysis technique used in this study is multiple regression with the help of calculations through the SPSS application. The calculation results show that the compensation variable has a positive and significant effect on employee loyalty, the work environment variable has a positive and significant effect on employee loyalty, and the workload variable has a positive and significant effect on employee loyalty. To increase employee loyalty, BPR Weleri Makmur should continue to maintain the compensation that has been given to its employees with salary, bonuses, incentives, allowances and facilities or others, then the importance of improving a good and conducive work environment atmosphere in helping to improve employee performance and loyalty in terms of lighting, room layout and design, comfortable room without noise and cool air temperature (air conditioner) at work.